Nailfold capillary density in 140 untreated children with juvenile dermatomyositis: an indicator of disease activity - Lauren M. Pachman; Gabrielle Morgan; Marisa S. Klein-Gitelman; Najah Ahsan; Amer Khojah (BMC, 2023)
Abstract Background We lack a reliable indicator of disease activity in Juvenile Dermatomyositis (JDM), a rare disease. The goal of this study is to identify the association of nailfold capillary End Row Loop (ERL) loss with disease damage in children with newly diagnosed, untreated JDM. Findings We enrolled 140 untreated JDM and 46 age, race and sex matched healthy controls, ages 2-17. We selected items from the Juvenile Myositis Registry for analysis. Variables include average ERL density of 8 fingers, average capillary pattern, hemorrhages, and clinical and laboratory correlates. Laboratory data includes Myositis Specific Antibodies (MSA), disease activity scores (DAS), Childhood Myositis Assessment Scale (CMAS), and standard clinical serologic data. The reduced mean ERL density is 5.1 ± 1.5/mm for untreated JDM vs 7.9 ± 0.9/mm for healthy controls, p < 0.0001, and is associated with DAS-skin, r = -0.27 p = 0.014, which did not change within the age range tested. Untreated JDM with MSA Tif-1-γ had the lowest ERL density, (p = 0.037); their ERL patterns were primarily "open" and the presence of hemorrhages in the nailfold matrix was associated with dysphagia (p = 0.004). Conclusions Decreased JDM ERL density is associated with increased clinical symptoms; nailfold hemorrhages are associated with dysphagia. Duration of untreated disease symptoms and MSA, modify NFC shape. We speculate nailfold characteristics are useful indicators of disease activity in children with JDM before start of therapy.